Analysis of P-wave Changes for Prediction of Atrial Fibrillation Episodes - Moreno Aramburu, Cristina; Martín Yebra, Alba; Savelev, Aleksei; Platonov, Pyotr; Laguna, Pablo; Martínez Cortés, Juan Pablo (Jornada de Jóvenes Investigadores del I3A, 2022)
Atrial fibrillation (AF) is the most frequent arrhythmia in clinical practice. It usually initiates as a paroxysmal activity (PxAF), with the subject having sinus rhythm, with interleaved AF episodes. The objective of the study is to evaluate the observations made by Pyotr Platonov, who hypothesized that slower conduction in the atria and the presence of fibrosis in the atrial myocardium, both associated to AF, lead to P waves widened, more complex and with increased rugosity. The study shows that P wave morphology significantly changes prior to the onset of AF episodes in PxAF, increasing the variability, making more complex P-wave loop, and enlarging the duration, which can be attributed to the de-structuring of the atrial wavefront.